Water movement and phosphorus leaching from managed and unmanaged grass buffer strips - Jack, Daniel (2016)
This study was undertaken in a long term field trial investigating the effect of grass buffer strips on nutrient leaching. The treatments included were harvested grass (HG), non-harvested permanent grass (PG) and cultivated soil without a buffer strip (control). Infiltration rate (IR), field saturated hydraulic conductivity (Kfs) and saturated hydraulic conductivity (Ks) were determined. In addition, rainfall simulation in the laboratory was conducted on soil cores (20 cm diameter, 20cm high) after these had been exposed to repeated freezing and thawing in the field for one month. Large spatial variability of hydraulic properties was demonstrated when comparing different treatments. Both PG and HG were shown to have a higher IR during the summer compared to the control. Levels of turbidity in the water were significantly higher (p≤0.05) in the control plots than PG plots. Water concentration of dissolved reactive phosphorus (DRP) was significantly (p≤0.05) higher in both PG and HG treatments than in the control. This was proposed to be due to mobilizing of P from vegetation during the freezing and thawing cycles. A linear regression model of TOC on DRP gave a coefficient of determination R2=0.45.